2017
DOI: 10.1371/journal.pone.0189339
|View full text |Cite
|
Sign up to set email alerts
|

Does cognitive impairment impact adherence? A systematic review and meta-analysis of the association between cognitive impairment and medication non-adherence in stroke

Abstract: BackgroundWhile medication adherence is essential for the secondary prevention of stroke, it is often sub-optimal, and can be compromised by cognitive impairment. This study aimed to systematically review and meta-analyse the association between cognitive impairment and medication non-adherence in stroke.MethodsA systematic literature search of longitudinal and cross-sectional studies of adults with any stroke type, which reported on the association between any measure of non-adherence and cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 45 publications
2
29
1
3
Order By: Relevance
“…The association between cognition and adherence is complex and not yet fully understood (27). While some studies found that cognitive impairment is, in general, a major predictor of nonadherence (28,29), a recent metaanalysis found no association between cognitive impairment and medication nonadherence in post-stroke patients (23). The Adheson study showed that in relation to the Morisky-Green test, patients with cognitive deterioration were 2.1 times more likely to take the treatment incorrectly (13).…”
Section: Prevalence Of Nonadherence and Its Association With Clinicalmentioning
confidence: 99%
“…The association between cognition and adherence is complex and not yet fully understood (27). While some studies found that cognitive impairment is, in general, a major predictor of nonadherence (28,29), a recent metaanalysis found no association between cognitive impairment and medication nonadherence in post-stroke patients (23). The Adheson study showed that in relation to the Morisky-Green test, patients with cognitive deterioration were 2.1 times more likely to take the treatment incorrectly (13).…”
Section: Prevalence Of Nonadherence and Its Association With Clinicalmentioning
confidence: 99%
“…Evidence for the association between cognitive impairment and non-adherence is inconsistent. In one pooled analysis, there was no evidence of an association between cognitive impairment and non-adherence [5]. It may, however, be important to distinguish between degrees of cognitive impairment, as individuals with more severe impairments and dementia may rely on caregivers to administer medication, leading to increased adherence.…”
Section: Adherence and Plausibilitymentioning
confidence: 95%
“…Although advances in carotid revascularization have contributed to the improvement in patient outcomes, the absolute effect on population level compared to a pharmacological secondary prevention is small [3]. Treatment of all major risk factors is estimated to reduce the risk of recurrent stroke by about 80% compared with no treatment [1,3] and optimum control of risk factors through the regular use of cardiovascular medication also reduces risk of cognitive impairment and cardiovascular events [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the conclusions from other studies that diabetes predisposes to cognitive decline both in humans and animal models [12,[30][31][32][33], and this finding also holds true for our study cohort who had TB and dysglycaemia. Cognitive decline may negatively affect compliance to the strict requirements of TB treatment including adherence to medications which can potentially worsen disease outcomes [34].…”
Section: Diabetes and Cognition Decline Among Tb Patientsmentioning
confidence: 99%